Marhata Sinamot at Toba Ethnic Wedding Ceremony: Antropolinguistics Study - Ma Samuel Rt Simanjuntak; Flansius Tampubolon; Jamorlan Siahaan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The scientific title is "Marhata Sinamot at the Toba Ethnic Wedding Ceremony: Anthropology Studies". This study aims to describe the performance, indexicality and participation of Marhata Sinamot at the Toba Ethnic Wedding Ceremony. The theory used to analyze the research data is the anthropolinguistic theory proposed by Duranti. By using descriptive method. The results obtained from this study are the performance in the Marhata Sinamot traditional ceremony in the Toba Ethnic community in general, namely Marhata Sinamot. In the Toba Batak community there are signs that are used as indexicality in the Marhata Sinamot traditional ceremony, namely, (1) traditional clothes, (2) ulos. And participants in the Marhata Sinamot ceremony have Dalihan Na Tolu, namely (1) Hula-hula, (2) Bone paranak, (3) Bone parboru, (4) Boru, (5) Dongan tubu, (6) Bere paranak, (7) Bere perboru and (8) Dongan Sahuta.